0 0

# solve using substitution y^2=x and x+2y+3=0

I need to solve using the substitution method, but i can't figure out how to do it with this problem. y^2 mean y squared.

If y^2=x, then you can substitute y^2 for x in the second equation, giving you y^2+2y+3=0.  Now that there's but a single variable (y), you should be able to solve as usual for y.  Once you have y, plug that number(s) into y^2=x and you'll have x.

The substitution method simply means that, given two equations, one can be reduced into a definitional statement, an equation that just tells you how to express one variable in terms of the other (in other words, an equation that starts with something like "x=" or ends with "=y").  You then substitute whatever's in the complicated side of this equation for the whichever variable is on the simple side in the OTHER equation, at which point you have a normal, one-variable version of the equation.

Thank you so much!
y2 = x
x + 2y + 3 = 0

Substitute y2 in place of x in the second equation, solve for y::

y2 + 2y + 3 = 0

y = [-2 ± √(22-4*1*3)]/2

y = -1 ± i√2

Solve for x:

x = y2 = [-1 ± i√2]2

x = 1-i2√2, -1+ i2√2